NEW SUBSTITUTED C(14)-ANDROGRAPHOLIDE DERIVATIVES WITH POTENT CYTOTOXIC ACTIVITIES - RAVINDRA PATIL,; VENKAT R. P,; VIROHIT PATIL ., (International Journal of Pharma and Bio Sciences, 2014)
Andrographolde is the major secondary metabolite from the plant Andrographis paniculata. It has been found to show cytotoxic activity. To improve the efficacy on cytotoxic activity, a series of new sulfonyl derivatives have been synthesized by structural modifications of the andrographolide at C-2 position. All the derivatives were tested for their cytotoxic activity against human small lung cancer (NCI-H187), leukemia K562, breast cancer (MCF-7/ADR) and lung adenocarcinoma (A549) cell lines. Most of the compounds have appreciable activity at tested cell lines. Compound 4a exhibited higher cytotoxic activity than parent compound andrographolide.